Teacher dimensions in pupils' science achievement - Reyes, Lourdes (Cubarrubia) 1905- (1969)
This study, which explores the teacher factor in pupil academic achievement, aims to provide the third dimension in the research activity of the U.P Science Education Center. It seeks to determine the set of teacher personality dimensions that differentiates "more effective" from "less effective" teachers, and the set of teacher personality dimensions which can be considered predictive of pupil academic performance in science and mathematics.
Thesis (Ph.D.Education)--University of the Philippines, Diliman.
Keywords: Teachers, Rating of -- Philippines; Science -- Study and teaching -- Philippines